Establishing load profile using remote metering system / Idzzuan Mohd Dahlan - Mohd Dahlan, Idzzuan (2007)
Energy efficiency is distinctly important in the economic trend of millenium. Efficient usage of energy will not only save but also helps to create healthy enviroment. This project paper discusses about the highly usage of load demand and power factors in UiTM Shah Alam.